Development of a Rapid Salivary Proteomic Platform for Oral Feeding Readiness in the Preterm Newborn - Khanna, Prarthana; Maron, Jill L.; Walt, David R. (Frontiers in Pediatrics, 2017)
Oral feeding competency is a major determinant of length of stay in the neonatal intensive care unit (NICU). An infant must be able to consistently demonstrate the ability to take all required enteral nutrition by mouth prior to discharge home. Most infants born prematurely (<37 weeks) will require days, if not weeks, to master this oral feeding competency skill. Inappropriately-timed feeding attempts can lead to acute and long-term morbidities, prolonged hospitalizations and increased healthcare costs. Previously, a panel of five genes involved in essential developmental pathways including sensory integration (NPHP4, PLXNA1), hunger signaling (NPY2R, AMPK) and facial development (WNT3) required for oral feeding success were identified in neonatal saliva. This current study aimed to translate these five transcriptomic biomarkers into a rapid proteomic platform to provide objective, real-time assessment of oral feeding skills, to better inform care and to improve neonatal outcomes. Total protein was extracted from saliva of ten feeding-successful and ten feeding-unsuccessful infants matched for age, sex and post-conceptional age (PCA). Development of immunoassays was attempted for five oral feeding biomarkers and two reference biomarkers (GAPDH, YWHAZ) to normalize for starting protein concentrations. Normalized protein concentrations were correlated to both feeding status at time of sample collection and previously described gene expression profiles. Only the reference proteins and those involved in hunger signaling were detected in neonatal saliva at measurable levels. Expression patterns for NPY2R and AMPK correlated with the gene expression patterns previously seen between successful and unsuccessful feeders and predicted feeding outcome. Salivary proteins associated with hunger signaling are readily quantifiable in neonatal saliva and may be utilized to assess oral feeding readiness in the newborn. This study lays the foundation for the development of an informative, rapid, proteomic platform to assess neonatal oral feeding maturation.